Comparative analysis of the 2019 results between juniors and seniors in women's artistic gymnastics at the world championships - Atikovic, A.; Delaš Kalinski, S.; Nožinovic Mujanovic, A.; Penjak, A.; Curic, M. (Acta Kinesiologica, 2020)
The subject sample was composed of (n=259) gymnasts who competed at the 49th FIG WAG Artistic Gymnastics Senior World Championships Stuttgart (GER) and (n=119) gymnasts who competed at the 1st FIG WAG Artistic Gymnastics Junior World Championships Gyor (HUN). The aim of this study was to determine the differences between the two age groups of gymnasts (juniors and seniors) in all the predictor variables by analysing the D, E and FS score. Difference between juniors and seniors is 5.474 years of age. In individual competitions there is no difference in qualifications between BBE, FXE, FXF and in the finals: VTE, UBE, BBE, BBF, FXF. In team competition, the highest scores are on the VT and the lowest on the BB. In all-around competitions there is no difference in qualifications between UBE, BBD, FXE, FXF, FS and in the finals: UBE, FXE. Average FS scores on vault are significantly higher than on all other apparatus.